Docker container python IDE - Gamaledin, Youssef Ehab; Keong, Lee Kim; Medi, Imran (Journal of Applied Technology and Innovation, 2022)
Current IDEs consume a high amount of disk memory while having poor usability. This project focuses on developing a browser-based Python IDE with a friendly and non-complex user interface developed based on user feedback, whilst consuming less disk memory by using Docker containers.